(untitled) (ENTHYMEMA, 2016)
The paper traces the very different contours of Soviet discourses of Arctic in the Stalinists 1930s with their narrative transformation of Arctic space into integral part of national Soviet space. The goal is to see how the Arctic narrative developed and evolved throughout the last 30/40 years of the Soviet era. The research is based on analysis of 3000 literary texts, articles, memoirs and letters, published and archived. The results confirm the presence of ‘Arctic discourse’ in the Soviet society and is supported by various sources. The Arctic issue became permanent in cultural and political practices of the time in the late 1920s and had a series of climaxes in the 1930s–1940s. Its popularity peaked in the mid-1950s and then dropped dramatically. The cultural and literary background of such change is explored through the narrative definitions.